Caracterização geomorfológica e morfométrica da Folha Alhandra (1:25.000) - Freitas, Gilvonete Maria Araujo de (2012)
With the aid of morphometric rates, the present work aimed at characterizing the geormorphology of the area corresponding to Alhandra Leaf 1:25.000, which is located mainly on Tabuleiros Litorâneos, formed largely by poorly consolidated sediments of Formação Barreiras. This geormorphology is associated with other elements of the physical environment with which the area studied keeps mutual interaction. In addition, this work searched for features that could indicate neotectonic action on the configuration of the relief and on the drainage pattern of the area. The forms of land occupation and use were also verified in comparison with the current legislation. Having this in mind, a bibliographical research was done in order to describe the theme and to characterize the geomorphological, geological, pedological and climatic aspects of the vegetation and the hidrography of the area. Considering the importance of geotechnology, we were able to describe more precisely the area by using the maps produced. With the level curves taken from Alhandra Leaf and the SPRING 5.1.7, hypsometric, clinographic and geomorphological maps were made. Also, by using the same software, satellite images, and field work, a map about the land occupation and use was produced. With the aid of the hypsometric and the clinographic maps, it was possible to measure the relief modeling and analyze the forms of land occupation and use, which were synthetised both in the land occupation and use map and also in the declivity irregular land occupation and use map, which was constructed by the overlapping of clinographic and land occupation and use maps. The geomorphological map made it possible to establish the chronological order (geological time), from the old soil formation to the most recent ones. Topographic profiles were constructed by the use of Microsoft Office Excel 2007 in order to observe details in the ground variation. As geomorphology is directly related to pedology, laboratory analyses were made (pH, soil density, particle density and granulometrics). Finally, Slope Length (SL) and drainage density (Dd) rates were created to investigate the drainage network with the aid of SPRING 5.1.7 software. The Slope Length (SL) rate was applied in order to verify the neotectonic influence, by correlating the results with the morphology of the relief. The drainage density (Dd) rate was used to identify points vulnerable to erosive processes and rates related to the production and to the transport of sediments, originated from interfluvial system. After applying and analyzing the technicaloperating procedures, we observed that the geomorphological features as well as the drainage pattern are the result of the conjunction of structural control, neotectonics and regional climatic factors. The possible neotectonic influence is evidenced by means of the tilted and scaled blocks and by means of the drainage network, through the abrupt inflexion of some river courses and right-lined channels. The climatic factors are mainly responsible for the denudational processes and for the erosive features, when associated with anthropic actions. With relation to land occupation and use, we noticed that the transgression of current legislation (Florest Code, 1965) is a common practice; areas with declivity superior to 12% as well as those very close to the river courses are occupied mainly with sugar cane crops.